Comparative analysis of chloroplast DNA of crytocoryne species - Muhammad Mustaqim, Haji Shamsudin (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study focuses on determining polymorphism of chloroplast DNA sequence in Cryptocoryne species. The emergence of new hybrid of C. purpurea in Sarawak and Borneo creates attention among scientists to determine possible mother plants for the species. Determination of possible mother plants for the hybrid through molecular work provides useful information for taxonomy study. One new hybrid of C. purpurea and three possible mother plants of the hybrid; C. cordata var. zonata, C. ferruginea and C. pallidinervia have been used. Polymorphism in chloroplast DNA in these Cryptocoryne species is determined through PCR amplification of rbcL gene sequence coded rubisco synthesis using primers rbcL-1 (5’-TGTCACCAAAAACAGAGACT-3’) and rbcL-2 (5’-TTCCATACTTCACAAGCAGC-3’), and restriction fragment digestion using several restriction endonucleases. Polymorphisms of certain restriction sites were obtained.